1997
DOI: 10.1111/j.1553-2712.1997.tb03718.x
|View full text |Cite
|
Sign up to set email alerts
|

Medical Clearance and Screening of Psychiatric Patients in the Emergency Department

Abstract: Objectives: To study the frequency of medical complaints and need for routine ED medical, laboratory, and toxicologic clearance for patients presenting with psychiatric chief complaints. Methods: A retrospective, observational analysis of psychiatric patients seen in an urban teaching hospital ED over a 2-month period was performed. The individual sensitivities of history, physical examination, vital signs, and complete blood counts and chemistry panels for identifying medical problems were determined. The sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0
9

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(58 citation statements)
references
References 13 publications
3
46
0
9
Order By: Relevance
“…In theory, of course, knowledge about exposure to drugs of abuse could potentially alter diagnosis and disposition from the emergency department. However, this study confirms several previous studies which have indicated that this is not the case (Table 4); [5][6][7][23][24][25][26]. Many of these studies are not prospective and have not attempted to account for other factors which might impact admission decisions by emergency clinicians.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In theory, of course, knowledge about exposure to drugs of abuse could potentially alter diagnosis and disposition from the emergency department. However, this study confirms several previous studies which have indicated that this is not the case (Table 4); [5][6][7][23][24][25][26]. Many of these studies are not prospective and have not attempted to account for other factors which might impact admission decisions by emergency clinicians.…”
Section: Discussionsupporting
confidence: 70%
“…In many emergency departments, however, the assessment of suicide risk is further performed by professional mental health workers. Commonly, these mental health workers request laboratory assessments of substance use, despite the fact that the utility of routine laboratory testing has been criticized in both experimental studies [5][6][7] as well as expert guidelines regarding the screening of psychiatric patients in the ED [8][9][10]. Nonetheless, at least one study has indicated that many emergency physicians are routinely required to obtain labs for psychiatric patients [11].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the older literature, more contemporary studies are finding much lower rates of unsuspected, clinically emergent, or urgent laboratory abnormalities. Two studies of adult ED patients with psychiatric complaints found low rates of clinically significant abnormalities on routine laboratory testing, 55, 67 the majority (94%) of which were clinically suspected on the basis of the patient's history and physical examination. 55 Similar results have been reported in admitted adult psychiatric patients after an ED evaluation.…”
Section: Diagnostic Laboratory Testing and Medical Clearancementioning
confidence: 99%
“…Two studies of adult ED patients with psychiatric complaints found low rates of clinically significant abnormalities on routine laboratory testing, 55, 67 the majority (94%) of which were clinically suspected on the basis of the patient's history and physical examination. 55 Similar results have been reported in admitted adult psychiatric patients after an ED evaluation. One study of 250 psychiatric inpatients found a mean of 27.7 tests were ordered per patient, with only 4% (11 of 250) having "important" medical problems discovered and less than 1 test in 50 resulting in any clinically useful information.…”
Section: Diagnostic Laboratory Testing and Medical Clearancementioning
confidence: 99%
“…This figure is higher than that previously reported. 14,15,20 A probable explanation is that 92% of the patients in this study had had no health care contact prior to this presentation. The effectiveness of our screening procedure …”
mentioning
confidence: 99%